Alcoholism and its consequences: psychical and physical aspects - Carneiro, Francisco Vilemar Pinto; Jorge, Maria Salete Bessa; Batista, Fátima Lúcia Ramos (Rev Rene, 2005)
Research about alcoholism and its consequences aimed at identifying the factors that interfere in the alcohol abstinence, at knowing the physical and psychical manifestations that take place during such abstinence, and at identifying the reasons that lead alcoholics to drink. This descriptive study was undertaken on 30 alcoholic patients in treatment at a Public Hospital in Fortaleza, Ceará, from January to February of 2003. The sample was composed of 27 men and 3 women within an age range of 15 to 54 years-old. Information was gathered through semi-structured interviews and the results were built up through the content analysis technique. The results have pointed out the main difficulties of alcoholics facing alcohol abstinence, in which stand out depression, social relationships, as well as physical alterations that affect health and quality of life. We concluded that the treatment and recovering depends on the interest and personal motivation, in addition to alternatives of support and help to the victim.